Rhodium(II)‐Catalyzed Synthesis of N‐Aryl‐N′‐tosyldiazenes from Primary Aromatic Amines Using (Tosylimino)aryliodinane: A Potent Stable Surrogate for Diazonium Salts. Issue 9 (8th March 2017) - Ito, Motoki; Tanaka, Arisa; Higuchi, Kazuhiro; Sugiyama, Shigeo
Abstract : A single‐step synthesis of N ‐aryl‐ N′ ‐tosyldiazenes from primary aromatic amines was developed. A wide range of aromatic amines provided the corresponding products in high yields by N–N bond formation with Rh II –nitrene intermediates, which were generated in situ from dirhodium(II) complex catalysts and (tosylimino)‐2, 4, 6‐trimethylphenyliodinane, followed by oxidation. The synthesized N ‐aryl‐ N′ ‐tosyldiazenes were successfully demonstrated to serve as potent and stable surrogates for diazonium salts in the two‐step deaminative transformation of primary aromatic amines. Abstract : N ‐Aryl‐ N′ ‐tosyldiazenes1 are obtained in a single step from aromatic amines2 by N–N bond formation with Rh II –nitrene, generated in situ from an iminoiodinane and a dirhodium(II) complex catalyst followed by oxidation. Synthesized diazene1 serves as a potent and stable surrogate for diazonium salts in the two‐step deaminative transformation of primary aromatic amines.